The Compatibility of Polyglycerol Acrylic as Plasticizer For Polyvinyl Chloride Matrix - Muhammad Yusuf (Jurnal Pendidikan Kimia (JPKim), 2016)
Abstract- The aim of this research was to compare whether polyglycerol (PG) acrylic plasticizer is more compatible and has good thermal stability than PG acetate plasticizer or even DOP plasticizer. PG acrylic plasticizer producted from polymerization of glycerol and then esterification with acrylic acid and can used as a plasticizer for PVC. Based on tensile strength and elongation analysis can be concluded that PG acrylic-DOP plasticizer (tensile strength 37.33 MPa and elongation 277.2%) is more compatible for PVC than DOP plasticizer (tensile strength 5.4 MPa and elongation 230.33%) and PG acrylic plasticizer (tensile strength 18.67 MPa and elongation 89.7%). PG acrylic-DOP plasticizer also more compatible than PG acetate plasticizer for PVC. According to DTA analysis can be concluded that PG acrylic plasticizer has thermal stability alike with PG acrylic – DOP plasticizer in PVC matrix and better compared with DOP plasticizer. This can be proven by the increase of decomposition (exoterm) temperature PG –acrylic plasticizer in PVC (from 490 oC to 500 oC) alike with PG acrylic-DOP plasticizer (constant 490 oC) andhigher than DOP plastcizer (from 490 oC to 400 oC). According to tensile strength, elongation and DTA analysis can be concluded PG acrylic-DOP plasticizer is a better plasticizer in PVC matrix than PG acrylic, PG asetate, and DOP plasticizer.   Keyword: polyglycerol acrylic, PVC, compatibility, and DTA